2009
DOI: 10.1177/1756283x09337645
|View full text |Cite
|
Sign up to set email alerts
|

Review: Effect of probiotics on gastrointestinal function: evidence from animal models

Abstract: Abstract:The digestive tract works through a complex net of integrative functions. At the level of the gut, this integration occurs between the immune, neuromotor and endocrine systems, the intestinal barrier and gut luminal contents. Gastrointestinal function is controlled and coordinated by the central nervous system to ensure effective motility, secretion, absorption and mucosal immunity. Thus, it is clear that the gut keeps a tightly regulated equilibrium between luminal stimuli, epithelium, immunity and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Animal models that described the beneficial effects of probiotics on the enteric nervous system (62) and intestinal motility (63) corroborate findings in humans.…”
Section: Management Strategiessupporting
confidence: 53%
“…Animal models that described the beneficial effects of probiotics on the enteric nervous system (62) and intestinal motility (63) corroborate findings in humans.…”
Section: Management Strategiessupporting
confidence: 53%
“…This allowed us to deduce how a certain symbiont and probiotic bacteria act on the ENS and thereby gut function. As this parallels the timing of effects on motility in ex vivo peristalsis preparations 10 , the actions of beneficial bacteria on intestinal motility are likely due to actions on neurons rather than second-order effects, which depend on initial involvement of the host's immune or endocrine systems 34 . This is underscored by our observation that killed JB-1 or LS that do not alter ex vivo motility, also failed to alter IPAN excitability, suggesting strain specificity for probiotic neuroactivity.…”
Section: Discussionmentioning
confidence: 87%
“…The other possibility is that physiologically active substances produced by the gut flora may have affected colon transit, regardless of the fold differences in the concentration of bacterial species. 12,[24][25][26] Several studies have demonstrated that administering probiotics or prebiotics such as Lactobacillus-enriched artichoke reduced visceral hypersensitivity and inflammation, or relieved symptoms of constipation, without altering bacterial populations. [26][27][28] Probiotics are capable of lowering intracolonic pH due to bacterial SCFA production.…”
Section: Discussionmentioning
confidence: 99%
“…30 Orally administered probiotics have been considered to target the motor and neural apparatus in post-infective gut dysfunctions. 25 Probiotics including lactic acid bacteria were shown to be effective for the relief of abdominal bloating in patients with diarrhea-predominant irritable bowel syndrome (D-IBS), but did not show a significant alteration in gut transit. 31,32 Studies involving the administration of a probiotic, B. lactis DN-173 010, showed improved colonic transit times in both a healthy population and constipated patients.…”
Section: Discussionmentioning
confidence: 99%